Spatial Analysis of Hospitalized Dengue Patients in Cabanatuan City: Demographics and Risk - Santos, Ronald S.; Tumibay, Gilbert M. (International Journal of Advanced Engineering Research and Science, 2022)
This study employed spatial pattern analysis of a prospective dengue epidemic in one of the cities in Nueva Ecija Philippines – Cabanatuan City. It aims to give strategic information for the dengue management effort in the face of constrained capacity. The researchers examined the demographic pattern of dengue cases to add to the knowledge needed for successful policy-making. Weekly records of dengue cases from multiple Disease Reporting Units (DRU) in Cabanatuan City were gathered as the database. This includes barangay, sex, age, and DRU types from January 2014 to December 2018. Each recorded dengue fever patient’s barangay was geocoded to map and clustered. This research found a substantial correlation between reported incidents and particular demographic groupings among male, age 10-14, mostly admitted in a government hospitals and weeks 28 to 42 where the virus transmission is high. Furthermore, the dynamic growth of the aggregation of disease incidence (hotspots) for dengue patients in Cabanatuan City was displayed using spatial analysis utilizing geographic information system (GIS). It is hoped that the research results shall provide strategic information for dengue control program planning and design.